Analysis of the Defect Level of Paving Stone DC 06 Products Using Six Sigma and FMEA Methods at PT. Duta Beton Mandiri Pasuruan - Kusniah, Qonita; Munir, Misbach (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
The rapid development of the industry requires companies to improve the quality of products to maintain competitiveness. PT. Duta Beton Mandiri Pasuruan faces the problem of the high defect rate of DC 06 paving stone products, reaching 30.75% in March 2020, which has an impact on financial losses and customer satisfaction. This study aims to identify the type and cause of defects, calculate sigma levels, and provide recommendations for improvement using Six Sigma and FMEA methods. A quantitative approach is used to calculate DPMO and sigma levels, while a qualitative approach is applied to analyze the causes of defects through observation and interviews. The results showed a sigma level value of 2.52 and a DPMO of 178,827, indicating low process performance. FMEA analysis identified gopel defects as the main problem with the highest RPN (245). Improvement recommendations include employee training, machine calibration, material supervision, and SOP refinement. The implementation of this proposal is expected to reduce the defect rate and increase production efficiency. This research makes a practical contribution to the application of Six Sigma and FMEA for quality improvement in the manufacturing industry